Emergency Flight Control Based on the Fan Wing - Lin Meng; Shuo Wang; Ye Chen; Yang Gao (International Journal of Aerospace Engineering)
FanWing has been taken to the visual field because of its performance combination of fixed-wing aircraft and helicopter. Its flight mode is currently limited mainly by a remote control, while the research of automated flight control is on the rise. The fan wing could offer lift, thrust, and the additional pitch moment for longitudinal control. At the same time, the roll moment and the yaw moment can be generated by the differential rotation of the cross-flow fan to realize the lateral control. It provides the possibility for its emergency flight control when the aerodynamic control becomes inefficient at a low speed. The difficulties in designing the emergency control system in both the longitudinal and lateral controls are analyzed. And it emphasizes the importance of selecting its center of gravity and the emergency control method of longitudinal control in engineering. The simulation results show that as an emergency flight control system, fan wing control is feasible. The study of the fan wing control will provide a reference solution for its further engineering applications.